Hypophosphatemia and Type-2 Diabetes Mellitus: A Review - Karmakar, Pijush; Mohiuddin, Mohammad; Nargish, Shaheen; Islam, Md Zakirul (Eastern Medical College Journal, 2024)
Type-2 diabetes is a global public health crisis that threatens the economies of all nations, particularly developing countries. Type-2 diabetes mellitus has been suggested to be the most common endocrine disorder associated with several metabolic disturbances including changes in serum calcium, zinc, magnesium, or phosphate. Moreover, those who have poor glycemic control and longtime diabetes mellitus are more likely to decrease the blood phosphate level. Low serum phosphate level may be associated with morbidity and mortality from cardiovascular disease in these patients. So, the findings of this study may suggest that serum phosphate is an important screening parameter in type-2 diabetic patients especially who have poor glycemic control and longtime diabetes mellitus. Eastern Med Coll J. July 2023; 8 (2): 45-50